Early breast cancer precursor lesions: lessons learned from molecular and clinical studies - Sinn, Peter; Elsawaf, Zeinab; Helmchen, Birgit; Aulmann, Sebastian (Breast care, 2010)
Atypical ductal hyperplasia (ADH), flat epithelial atypia (FEA), and lobular neoplasia (LN) form a group of early precursor lesions that are part of the low-grade pathway in breast cancer development. This concept implies that the neoplastic disease process begins at a stage much earlier than in situ carcinoma. We have performed a review of the published literature for the upgrade risk to ductal carcinoma in situ or invasive carcinoma in open biopsy after a diagnosis of ADH, FEA, or LN in core needle biopsy. This has revealed the highest upgrade risk for ADH (28.2% after open biopsy), followed by LN (14.9%), and FEA (10.2%). With LN, the pleomorphic subtype is believed to confer a higher risk than classical LN. With all types of precursor lesions, careful attention must be paid to the clinicopathological correlation for the guidance of the clinical management. Follow-up biopsies are generally indicated in ADH, and if there is any radiological-pathological discrepancy, also in LN or FEA.